Perlindungan Hukum bagi Pemohon Sertifikat dalam Program PTSL yang Perolehan Haknya Berdasarkan Pernyataan Hibah Sepihak - Prayitno, Bayu Agung; Permadi, Iwan (Universitas Negeri Malang, 2021)
This study aimed to analyze the form of legal protection for certificate applicants in the Complete Systematic Land Registration (PTSL) program whose transfer of land rights was obtained from a grant with a unilateral statement without going through a grant deed. The method used in this research was normative juridical research. This study used a statute approach and a conceptual approach. In Indonesian positive law, a unilateral statement can be used as ownership of land obtained through a grant. The willingness of the heirs to make an authentic deed before the PPAT was an effort to strengthen the legal protection of the ownership of land rights that resulted from the grant.